A new finite-time average consensus protocol with boundedness of convergence time for multi-robot systems. (13th November 2017) - Wang, Xiaobo; Li, Juelong; Xing, Jianchun; Wang, Ronghao; Xie, Liqiang; Chen, Ying
Multi-robot consensus has been extensively applied in robotics. In this study, a new protocol is proposed to solve the finite-time average consensus problem. The protocol can improve the convergence rate. The upper bound of the convergence time is obtained. Analysis shows that there exists a limit value of the convergence time when the disagreement of initial states tends to be infinitely large, and the value is irrelevant to the initial states. The relationship between convergence time and initial states, communication topology, parameter is analysed. Lastly, the effectiveness of the results is verified by simulations.